Environmental managing in area occupied by a cemetery in the city of Seberi – RS - Kemerich, Pedro Daniel da Cunha; Borba, Willian Fernando de; Flores, Bruno Acosta; Pretto, Pablo Ricardo Piceti; Descovi Filho, Leonidas Luiz Volcato (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611709161 The areas of cemeteries are becoming the target of many researches nowadays. Studies show in some cases, contamination of soil and groundwater caused by clearance of the bodies. In this study, we conducted a survey of the situation of St. John the Baptist Cemetery in the Brazilian city of Seberi – RS and the vulnerability of contamination of the aquifer by the GOD methodology proposed by Foster et al. (2006), which recorded the presence of 1509 graves, some still built in the times of its foundation (1930). It was noted the neglect of family members with the graves, many in disrepair and some abandoned, being outside the rules proposed by CONAMA resolution 335/2003 which provides for the environmental licensing of areas occupied by cemeteries.